THE DYNAMICS OF JAMAAH TABLIGH'S METHODS: AN EXAMINATION OF SPIRITUAL AND SOCIAL IMPACT IN PAROMPONG WEST BANDUNG - Hakim, Ajid; Supianudin, Asep; Tarpin, Tarpin; Djalil, Maman Abdul; Fadjriudin, Fadjriudin (Al-Tsaqafa : Jurnal Ilmiah Peradaban Islam, 2024)
There are several interesting things about the Jamaah Tablig movement (JT), especially in Indonesia. These interesting phenomena include, first: the method of da'wah. JT's da'wah method is considered unique and contradictory. In its da'wah method it requires to leave the family for a certain time. So that, this method requires its members to leave work and family. This of course has an impact on family livelihood and productivity. Meanwhile, earning a living for the family is considered an obligation in sharia. This is the first contradictory and unique condition. But on the other hand, this contradictory condition is followed by another condition. This condition of spiritual change certainly cannot be done by individuals or other pious organizations. This event only exists among the JT tradition. This article discusses the movement and influence of Jamaah Tabligh in Parongpong, West Bandung. Keywords: Da'wah, Jemaah Tabligh, Parongpong, Khuruj, Sharia